A Teoria da Transcriação de Haroldo de Campos: uma leitura de Parmênides de Eleia - Lima, Ítalo Vieira (2022)
This dissertation has as its theme a poetic translation of Elea's Parmenides fragments, except for fragment VIII. Its approach starts from comparative literature, understood as an interdisciplinary approach, in which philosophy, translation studies, literary history, mythology, and other knowledge participate; here determined from Haroldo de Campos and his theory of poetic transcreation; because of its theme – the surviving fragments of a Greek philosopher poet from the 6th century BCE – it is inserted in classical studies, specifically, investigating the Greek hexameter and the proposals for its translation into Brazilian Portuguese; the contribution of other theorists linked to comparative literature, poetics, and literary translation will not be disregarded. Finally, it seeks to produce a poetic text parallel with that originating in ancient Greece, that is, a transcreation of Parmenides of Elea.